P39. The split hand syndrome in ALS and post-polio-syndrom. Issue 8 (August 2018) - Hoheisel, M.; Burmeister, L.; Tesch, M.
Abstract : Introduction: Electrodiagnostic evaluation for amyotrophic lateral sclerosis (ALS) relies on extensive measurements. As one diagnostic clue, the split-hand-index (SHI) was proposed. It compares the compound muscle action potential (CMAP) of the abductor pollicis brevis (APB) muscle with the CMAP of the abductor digiti minimi (ADM) muscle. In ALS, asymmetric atrophy of APB and ADM results in the index being reduced compared to the healthy population. This holds true despite the fact, that there is the same segmental innervation C8 for both examined muscles, as was previously discussed. Several studies have shown a diagnostic value in differentiating ALS from other motorneuron-diseases by means of the SHI, claiming a specific form of neurodegeneration in ALS, which is less marked for example in lower motor neuron disease (LMND), spinal muscle atrophy (SMA) or Hirayama disease. In our study, we aimed to compare the SHI of ALS-patients with our cohort of patients with post-polio-syndrome (PPS) to find out, whether it has a discriminative value in these patients too and to add knowledge to the proposed neuroscientific explanations of asymmetric thenar/hypothenar-atrophy. Methods: We conducted a retrospective analysis of our post-polio cohort since 1997. All patients were screened whether CMAPs of APB and ADM were collected. For comparison, we screened electrodiagnostic reports of all patients with a diagnosis of ALS for collected CMAPs of APB and ADM. We excluded patients with neuropathy of the median nerve (NMN) by means of a prolonged distal motoric latency (>4, 4 ms). Finally we randomly chose the same number of patients from our reports in that time period with normal results (NR), by excluding diagnosis of NMN, acute polyneuropathies and radiculo- and plexopathies of the arm. We calculated the SHI by dividing the CMAP of APB by the CMAP of ADM. Results: We found a significant difference ( p  = 0, 01) of the SHI between ALS patients (0, 97 ± 0, 84) and the NR-group (1, 26 ± 0, 72). The SHI of the PPS-group (0, 91 ± 0, 55) was not significantly different compared to the NR group ( p  = 0, 08), but showed a trend. Comparing the ALS-group with the PPS-patients, we found no statistically relevant difference ( p  = 0, 83). Discussion: As expected, we could reproduce a significant decrease of the SHI in ALS patients. However our results showed no statistically relevant difference between ALS-patients and PPS-patients when comparing the SHI. There is a broader distribution of values in the PPS-group, including cases of very high grade asymmetric atrophy of APB and ADM. A low SHI therefore is of no help in differentiating PPS from ALS-patients. As a limitation of our study it is important to acknowledge the retrospective study type and a possible selection bias of patients who suffer from an already clinically visible asymmetry, possible increasing electrodiagnostic evaluation numbers of the hand.